The way to Rio Luna - Córdova, Zoraida (Scholastic Inc., 2022)
Eleven-year-old Danny Monteverde believes in magic, he believes that the enchanted land of Rio Luna in his older sister's favorite book is real, and most of all he believes that if he can find the way to Rio Luna he will find his sister, Pili, there, because he does not believe that his sister would run away from the group home where they lived and leave him behind; but after years of being passed from one foster family to another, his faith begins to fade--until one day he finds a mysterious book in the library that contains a map to Rio Luna ... and a way to find Pili.